Mobility of 〈c+a〉 dislocations in zirconium. (15th September 2020) - Soyez, Thomas; Caillard, Daniel; Onimus, Fabien; Clouet, Emmanuel
Graphical abstract: Abstract: Plasticity in hexagonal close-packed zirconium is mainly controlled by the glide of dislocations with 1 / 3 〈 1 2 ¯ 10 〉 Burgers vectors. As these dislocations cannot accommodate deformation in the [0001] direction, twinning or glide of 〈 c + a 〉 dislocations, i.e. dislocations with 1 / 3 〈 1 2 ¯ 13 〉 Burgers vector, have to be activated. We have performed in situ straining experiments in a transmission electron microscope to study the glide of 〈 c + a 〉 dislocations in two different zirconium samples, pure zirconium and Zircaloy-4, at room temperature. These experiments show that 〈 c + a 〉 dislocations exclusively glide in first-order pyramidal planes with cross-slip being activated. A much stronger lattice friction is opposing the glide of 〈 c + a 〉 dislocations when their orientation corresponds to the ⟨ a ⟩ direction defined by the intersection of their glide plane with the basal plane. This results in long dislocations straightened along ⟨ a ⟩ which glide either viscously or jerkily. This ⟨ a ⟩ direction governs the motion of segments with other orientations, whose shape is merely driven by the minimization of the line tension. The friction due to solute atoms is also discussed.